'War conducted under certain rules, but nonetheless war': arbitration, capital and labour in the Western Australian gold mining industry, 1901-14 - Segal, Naomi (Australian Society for the Study of Labour History, 2007)
Between 1900 and 1914 state arbitration in the mining industry in Western Australia, was driven more by the mining employers and less so by organised labour. The process and outcome of centralised wage fixing reflected the different logics of the protagonists' collective actions, which arose from the inequality of their resources, both strategic and material, and from the differences in the nature and difficulty of their organisational tasks. Collective relations changed from arbitrated to unmediated conflict as the organisational, market and political power of labour grew. Arbitration, rather than resolving conflict, became the focus of disputes. Wider and more intense conflicts centering on the Awards of the Court were only averted by global considerations of overseas controllers of the mines for whom the declining Western Australian mines were only marginal. At the end of the period studied, Western Australian mining employers, while continuing to demonstrate cohesion and capacity for action superior to labour's, began forming and supporting new forms of industrial and political organisation with which to maintain their advantage over labour.